Strukturasi dalam Proses Gatekeeping pada Program Berita Patroli Episode Kriminal Kekerasan Seksual di Indosiar - Isti Nurul Khadizah; A Yudo Triartanto; Akhmad Syafrudin Syahri (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This study aims to explore structuration within the gatekeeping process of the Patroli news program in an episode reporting a case sexual violence aired on Indosiar. The research adopts a qualitative approach using the case study method. Data were collected through in-depth interviews and content analysis of the episode covering a case sexual assault committed by a resident doctor at Dr. Hasan Sadikin hospital, Bandung. The key informant in this study was the executive producer of the Patroli news program. This research employs two theoretical frameworks: Anthony Giddens’ structuration theory and Joseph A Devitto’s gatekeeping theory. The findings reveal that the Patroli news team enforces strict editorial control to avoid regulatory sanctions or public complaints. The program complies with the national journalistic standards, specifically the P3SPS broadcasting guidelines and the journalistic code of ethics. The Study concludes that Giddens’ three dimension of social structure signification, domination and legimitation are evident in the gatekeeping process, these structure, alongside the concept of gatekeeping as the filtering of news content, play significant role in shaping how sensitive criminal cares are selected and presentend to the public.